An Error Analysis Case Study: Out of Context Translation of Persian Sentences into English for Elementary EFL Learners - Yasin Khoshhal (ÜNİVERSİTEPARK Limited, 2017)
This study aims at analyzing errors committed by the Iranian elementary EFL learners. The investigation not only considers the types of errors committed, but also tries to shed light on the sources of these errors. To this end, a worksheet of ten Persian sentences translated from the original English content of the learners' course book were provided to a class of 20 elementary level English students. The learners were tasked with translating each sentence back into English. The researcher then had to analyze each translated sentence with regard to three aspects of grammar, choice of words, and spelling. The next step was categorizing any errors and finding the frequency of each of them. The results indicated that errors in the use of articles were the most frequent (20% of the total number of errors), followed by the wrong uses of verbs (18.66%), and the wrong use of tense (10.66%). According to the findings, correct use of articles should more often be the focus for EFL context, and the use of correct verbs and tenses should also be absolutely clarified and emphasized.